Gel Phantom Models for Radiofrequency and Microwave Ablation of the Liver - Chen, Willa J.; Wang, Qi; Kim, Charles Y. (Digestive Disease Interventions, 2020)
Heat-based percutaneous thermal ablation techniques have emerged as popular and effective treatments for liver cancer. As the technology continues to evolve, there is a need for optimized methods for experimentation to identify advantageous modifications and developments. Given that assessing and comparing resulting ablation zones in animal models are costly and resource-intensive, in vitro gel phantom models can serve an important role for early-stage experimentation. There exist several gel phantom recipes that have been reported in the literature. In this review, we will review the various recipes, the pros and cons to the existing models, and future potential directions.
Keywords: gel phantom; radiofrequency ablation; microwave ablation